Rising awareness to improve conservation of microorganisms in terrestrial ecosystems: advances and future directions in soil microbial diversity from Chile and the Antarctic Peninsula - Lavergne, Céline; Cabrol, Léa; Cuadros-Orellana, Sara; Quinteros-Urquieta, Carolina; Stoll, Alexandra; Yáñez, Carolina; Tapia, Joseline; Orlando, Julieta; Rojas, Claudia (Frontiers in Environmental Science, 2024)
Soil ecosystems are important reservoirs of biodiversity, as they are the most diverse habitat on Earth. Microbial biodiversity plays key roles in many ecosystem services, including the support to biogeochemical cycles. However, despite great advances in the understanding of the role of soil microbiota in providing benefits to nature and humankind, there is still much knowledge to be gained from understudied areas across the globe. Indeed, underrepresentation of the Global South in ecological studies has been suggested as an important gap that could compromise global solutions to conservation and the current biodiversity and climate crisis. In the Southern hemisphere, the southwest of South America, which includes Chile, runs behind the rest of the continent on studies related to soil microbial diversity and ecosystem functions. Therefore, to gain a better understanding of the global biodiversity and environment crisis, essential perspectives and knowledge from underrepresented regions need to be acknowledged to avoid biases in the scientific community. The main objective of this work is to understand how soil microbial diversity has been studied in Chile and the Antarctic Peninsula since 1975 to identify main knowledge gaps and funding opportunities for future research. Our survey consists of 343 articles representing 1335 sampling points from Continental Chile to the Antarctic Peninsula. It revealed a better representation of articles studying bacterial and fungal diversity in the extreme regions of Chile funded by both international funds and the National Agency for Research and Development (ANID). To study microbial diversity, cultivation-based methods are still the most commonly used, whereas molecular studies are increasing but insufficiently applied. We have identified and argued the need to enhance collaborative multi- and interdisciplinary efforts, fundings for sequencing effort, and long-term studies to provide robust and informative knowledge about soil microbial communities.